Factors Associated With Hospital Readmission of Heart Failure Patients - Al-Tamimi, Maitha Abdul-Aziz; Gillani, Syed Wasif; Abd Alhakam, Mohamed Elhassan; Sam, Kishore Gnana (Frontiers in Pharmacology, 2021)
Background: Heart failure (HF) is a significant cause of mortality, morbidity and impaired quality of life and is the leading cause of readmissions and hospitalization. This study aims to identify the factors contributing to readmission in patients with HF. Methods: A prospective-observational single-centre study was conducted in Sheikh Shakhbout Medical City, Abu Dhabi, United Arab Emirates. A total of 146 patients with HF are included in the study. Patient's demographics, patient medical characteristics, lab values, medications were collected for each patient, and the factors associated with readmission are identified. The primary outcome is to identify the factors contributing to readmission and reduce readmission rate. SPSS software for windows version 26 is used for data analysis. Results: The number of patients with heart failure admitted to hospital is higher with males (73.3%) than females. 42.1% were readmitted and were not compliant, whereas patients who are not readmitted and were compliant shows a lower percentage. Noncompliance was the most significant factor associated with readmission (P= 0.02, OR=3.6, 95%CI: 1.57 - 8.28). Other factors that are associated with readmission were low haemoglobin (P= 0.001, OR=0.96, 95%CI: 0.94 - 0.98), and NYHA class of HF (P=0.023, OR=2.22, 95%CI: 1.12 - 4.43). In addition, there are other factors that are linked with the disease but were not associated with readmission in our findings such as hypertension, coronary artery disease, gender, systolic blood pressure on admission, and age. Majority of the readmitted patients were NYHA Class IV 32/57 (56.1%) against 20/89 (22.7 %) in non-readmission group. Length of stay is (Median±IQR, 6±8.5). Conclusion: The study has revealed that noncompliance, low haemoglobin and NYHA Class IV of HF were the main factors associated with readmission. Clinical pharmacist as a team member could help to improve adherence in order to reduce the rate of admission.